ANALISIS KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PABRIK TAHU DAN TEMPE SERONI DI SANGATTA KABUPATEN KUTAI TIMUR - Mohammad Fathur Al Hadi; Prapdop; Hasmah (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
The purpose of this study was to analyze product quality and price partially or simultaneously influence purchasing decisions at the Seroni Tofu and Tempe Factory in Sangatta. The approach used in this research is a quantitative approach. In this study using multiple linear regression analysis. The source of data used in this study is primary data, namely questionnaires from respondents who have bought tofu at the Seroni Tofu and Tempe Factory. The results of the study indicate that product quality and price have a positive effect partially or simultaneously on purchasing decisions at the Seroni Tofu and Tempe Factory. The type of research used is an empirical study